Education as philosophies of engagement. Issue 5 (16th April 2018) - Peters, Michael A.; Besley, Tina; White, Jayne
Abstract: This is Introduction to the PESA conference 2014 held in Hamilton, NZ, is devoted to the conference theme of 'Education as philosophies of engagement'. We provide a brief analysis of the modern history of 'philosophies of engagement' since the Second World War examining the notion of socially responsible writing and teaching.